2015
DOI: 10.1590/s0102-67202015000300009
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Hla Dq2 and Dq8 in Patients With Celiac Disease, in Family and in General Population

Abstract: Background: Celiac disease is an enteropathy characterized by gluten sensitivity and broad clinical aspect. Has a multifactorial cause and depends on genetic, immunological and environmental factors for its development. The genetic influence is given mostly by the human leukocyte antigens HLA DQ2 and DQ8. Aim: To evaluate the prevalence of human leukocyte antigens DQ2 and DQ8 in three different groups: patients with celiac disease, first-degree relatives and the general population. Method: Retrospective analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 12 publications
3
33
1
4
Order By: Relevance
“…When counting only HLA DQ2.5cis and DQ8 the percentages in our study were: DQ2.5cis: 25% (572/2293), DQ8: 16% (361/2293), and 2.5cis and/or DQ8: 41% (933/ 2293), comparable to the 22% among the control group in a Swedish study for DQ2.5, 26 but higher for DQ8 than numbers from Mexico and Brazil. 27,28 Compared with the prevalence table of different populations in Alarida et al, 29 our numbers are higher for DQ2 (DQ2:31%/DQ2.5 25% vs 23%), but comparable for DQ8 (DQ8 16% vs 28.3%), and the Scandinavian numbers from the table (11% DQ2 and 15% DQ8) are lower than ours. Our HLA DQ2/8 prevalence is also higher than the one found in a screening study from Latvia comparable to our study.…”
Section: Discussioncontrasting
confidence: 55%
“…When counting only HLA DQ2.5cis and DQ8 the percentages in our study were: DQ2.5cis: 25% (572/2293), DQ8: 16% (361/2293), and 2.5cis and/or DQ8: 41% (933/ 2293), comparable to the 22% among the control group in a Swedish study for DQ2.5, 26 but higher for DQ8 than numbers from Mexico and Brazil. 27,28 Compared with the prevalence table of different populations in Alarida et al, 29 our numbers are higher for DQ2 (DQ2:31%/DQ2.5 25% vs 23%), but comparable for DQ8 (DQ8 16% vs 28.3%), and the Scandinavian numbers from the table (11% DQ2 and 15% DQ8) are lower than ours. Our HLA DQ2/8 prevalence is also higher than the one found in a screening study from Latvia comparable to our study.…”
Section: Discussioncontrasting
confidence: 55%
“…[15][16][17][18] Shared genetic predisposition, especially HLA-DR3 and immune cross-reactivity between gluten proteins and self-antigens could be the biological links behind the two diseases. [19][20][21] This association was later observed in epidemiological studies as well although the results were inconsistent. [21][22][23][24] This systematic review and meta-analysis was conducted with the aim to summarize all available evidence to assess the risk of sarcoidosis among patients with celiac disease compared with individuals without celiac disease.…”
Section: Introductionmentioning
confidence: 81%
“…Interestingly, several case reports have suggested a possible relationship between celiac disease and sarcoidosis . Shared genetic predisposition, especially HLA‐DR3 and immune cross‐reactivity between gluten proteins and self‐antigens could be the biological links behind the two diseases . This association was later observed in epidemiological studies as well although the results were inconsistent .…”
Section: Introductionmentioning
confidence: 99%
“…There are some indications that NCWS belongs to the group of the gluten-related disorders. The relatively large number of relatives with CD in srGS individuals could indicate a shared (genetic) predisposition, although current literature is not consistent about the relationship between HLA-DQ2 and NCWS [26,27,28]. Another indication for (mild) immune activation in NCWS comes from a study which showed that serum levels of soluble CD14 and lipopolysaccharide-binding protein as well as antibody reactivity to microbial antigens are elevated in NCWS patients with resolution after a GFD [29].…”
Section: Discussionmentioning
confidence: 99%